Penggunaan Bahasa Nonverbal dalam Upacara Adat Pernikahan Gaya Yogyakarta: Kajian Simbolik Etnopragmatik - NFN Pranowo (Ranah: Jurnal Kajian Bahasa, 2020)
This research is an interpretive reflective research with ethnopragmatic symbolic study theory. The source of the research data was taken from the documents of two makeup artists from Yogyakata, namely the makeup dresser Lisandra and the makeup dresser Hj. Rochayati. The research data are in the form of Javanese traditional wedding document of Yogyakarta style. The data collection technique is in the form of observation of photo documentation to obtain data in the form of a marriage ceremony sequence that uses verbal and nonverbal language from preparation to the end. The data analysis technique is interpretive reflective. The concrete steps of data analysis are (a) identifying documents, (b) classifying the sequences of marriages, and (c) interpreting each stage of the ceremony. The objectives of the research are (1) to describe the form of nonverbal language in traditional marriage ceremonies, and (2) to describe the non-verbal symbolic meaning of non-verbal language in marriage ceremonies. The findings of the research are that (a) the form of Yogyakarta-style traditional wedding events there are 15 stages, ranging from paningsetan to reception, and (b) ethnopragmatic symbolic meaning in general in the form of prayer requests so that what is desired can be realized.